Effect Functions on Goals of Health System in Iran - Somayeh Shahri; Seyed Jamalledin Tabibi; Amir Ashkan Nasiripour; Farhad Ghaffari (Tehran University of Medical Sciences, 2017)
Background and Aim: An assessment framework is necessary in order to achieve the goals of health system in any country. The current study was done with the aim of measuring the effects of the aspects of performances on realization of health system goals. Materials and Methods: This study was a cross-sectional, descriptive-analytic which was carried out during the years 2014-2015.  Four hundred and nineteen experts among all experts in the area of health by snowball and cluster sampling participated in the study. Collecting data was performed through the questionnaire of Health System Perfomance Assessment. The questionnaire's validity was confirmed using content validity method and its reliability was confirmed using Cronbachchr('39')s alpha coefficient. Data was analyzed by means of Pearson correlation coefficient test and Regression using SPSS 22 software. Results: The results of Pearson correlation coefficient test showed that the two component functions on equitable access to health services, the functions of protection against financial risks and actions on targets were equal to 0/827, 0/655 and 0/870. Respectively the results of the test showed 87% of the variance explained the aims of the functional components. Thus, we conclude that the functions of the financial risk for changes in standard deviation units and functions on equitable access to health services was as much as 0/655, and 0/827 predictable. Conclusion: Since the aspects of performances influence the realization of health system goals, investigating the effects of performances on the health system goals can help policymakers and managers to improve the performance through identifying weaknesses and strengths, review of interventions and healthcare reform, and the management of the health system.